Synthesis and electrochemical properties of Mn-doped Li2Mn0.1Ti1.9(PO4)3 materials - Sun, Lixia; Hu, Jiayan; Bai, Weiqi; Mao, Wutao; Song, Zhongcheng (Frontiers in Chemistry, 2023)
The hunt for a higher power storage, relatively inexpensive, non-polluting battery technology is currently a pressing issue because of the rapid growth of the worldwide economic and the progressively significant environmental pollution. Among the possible nanomaterials for rechargeable batteries that can have heteroatoms applied to it in order to improve its electrochemical behavior is LixTiy(PO4)3. Carbon-coated Mn-doped Li2Mn0.1Ti1.9(PO4)3 materials was synthesized by spray drying method. The material was characterized by XRD, SEM, TEM, BET, TGA et al. Crystal data refinement results by Rietveld method showed that the symmetry space group is Pbcn. The lattice parameters of Li2Mn0.1Ti1.95(PO4)3 are a = 11.9372 Å, b = 8.5409 Å, c = 8.5979 Å, = = = 90 , V = 876.59 Å3 and Z = 4). Rietveld refinement was performed, and the confidence factors are Rwp = 11.79%, Rp = 9.14%, and 2 = 1.425. It was exhibited that LMTP0.1/CA-700 material has good crystallinity. Testing the cells with LAND test procedure (200 mA/g current density for 200 cycles), the LMTP0.1/CA-700 material has a discharge specific capacity of about 65 mAh/g. The capacity decayed by only 3% during the cycle. It has some potential application values as cathode of lithium ion battery in the future.